2019
DOI: 10.1098/rsbl.2019.0227
|View full text |Cite
|
Sign up to set email alerts
|

Multi-network-based diffusion analysis reveals vertical cultural transmission of sponge tool use within dolphin matrilines

Abstract: Behavioural differences among social groups can arise from differing ecological conditions, genetic predispositions and/or social learning. In the past, social learning has typically been inferred as responsible for the spread of behaviour by the exclusion of ecological and genetic factors. This ‘method of exclusion’ was used to infer that ‘sponging’, a foraging behaviour involving tool use in the bottlenose dolphin ( Tursiops aduncus ) population in Shark Bay, Western Australia, was so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…NBDA 39,41,59 assumes that the rate of social transmission between individuals is proportional to the network connection between them and its aim is twofold: (1) to detect and to quantify social transmission and (2) to establish the typical pathways of social transmission. We used a multi-network NBDA 8,48 allowing us to input multiple networks, each scaled by a different s parameter, which estimates the rate of transmission per observation through each network 39 . We used the order of acquisition (OADA) variant of NBDA 40 , which takes as data only the order in which individuals acquire the target behavior and not the times of acquisition.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NBDA 39,41,59 assumes that the rate of social transmission between individuals is proportional to the network connection between them and its aim is twofold: (1) to detect and to quantify social transmission and (2) to establish the typical pathways of social transmission. We used a multi-network NBDA 8,48 allowing us to input multiple networks, each scaled by a different s parameter, which estimates the rate of transmission per observation through each network 39 . We used the order of acquisition (OADA) variant of NBDA 40 , which takes as data only the order in which individuals acquire the target behavior and not the times of acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…The study of social learning has been recently enriched by the integration of social networks analysis and associated statistical methodologies 5 . Such complementary approaches allow researchers to test for social transmission in wild freely interacting populations of animals and track the diffusion of behavioral innovations across social networks such as the spread of "lobtail feeding" in humpback whales 6 , new tool use in chimpanzees 7 and bottlenose dolphins 8 or new foraging techniques in great tits 9 . Social network structure has been found to shape the diffusion of socially learned behaviors; association of individuals in close proximity can be used to predict innovation spread 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…I present the basic latent variable model first, and then discuss expansions of the model to account for edge and node specific covariates, and spatial and temporal effects. I illustrate this modelling framework with an example analysis with Stan-a Bayesian general purpose inference library (Carpenter et al, 2017)-using a publicly available dataset on bottlenose dolphins (Wild et al, 2019a)…”
Section: Introductionmentioning
confidence: 99%
“…Information state can also determine the maintenance of social bonds-having similar social traits can facilitate cohesion among individuals by allowing them to synchronise and coordinate their activities(Coussi-Korbel & Fragaszy 1995). For example, populations of bottlenose dolphins are often divided into social communities assorted by learnt foraging tactics(Mann et al 2012;Machado et al 2019;Wild et al 2019), illustrating the idea that the more individuals interact, the more opportunities they have for copying each other, thus highlighting how social decisions can reinforce behavioural homogeny. Models have shown that the feedback between information transmission and social decision-making can stimulate the formation of stable groups within otherwise unstructured, well-mixed, populations with(Cantor et al 2015) and without any complex decision-making(Cantor & Farine 2018).…”
mentioning
confidence: 99%